The Cognitive and Social Lives of Paradigms in Information Science - Budd, John M; Hill, Heather (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Thomas Kuhn’s ideas, particularly of paradigm, are used with some frequency in information science. The usages of paradigm and the problematic nature of Kuhn’s thought are explored. Alternatives to Kuhn are suggested as a way out of the confusion his thought leads to. Les idées de Thomas Kuhn, plus particulièrement le paradigme, sont utilisées assez fréquemment en science de l’information. Les utilisations du paradigme et la nature problématique de la pensée de Kuhn sont explorées. Afin de contrer la confusion entourant la pensée de Kuhn, des alternatives sont proposées.